2005
DOI: 10.1111/j.1365-2672.2005.02639.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characterization of a novel chitinase from Bacillus thuringiensis subsp. kurstaki

Abstract: Aims: The present work aims to study a new chitinase from Bacillus thuringiensis subsp. kurstaki. Methods and Results: BUPM255 is a chitinase-producing strain of B. thuringiensis, characterized by its high chitinolytic and antifungal activities. The cloning and sequencing of the corresponding gene named chi255 showed an open reading frame of 2031 bp, encoding a 676 amino acid residue protein. Both nucleotide and amino acid sequences similarity analyses revealed that the chi255 is a new chitinase gene, presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
50
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(51 citation statements)
references
References 31 publications
1
50
0
Order By: Relevance
“…Bacillus thuringiensis (Bt) also produces chitinases (4)(5)(6). Several studies have reported that chitinases generated by Bt are involved in its antifungal activity and can enhance the insecticidal activity of Bt strains (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…Bacillus thuringiensis (Bt) also produces chitinases (4)(5)(6). Several studies have reported that chitinases generated by Bt are involved in its antifungal activity and can enhance the insecticidal activity of Bt strains (7)(8)(9)(10).…”
mentioning
confidence: 99%
“…However, the production of chitinase increased steadily during vegetative growth and reached a maximum after 70 h [11]. In this study, expression from the chiA promoter seemed to start at the post exponential growth phase (6 h) and almost reached a maximum at the middle of the stationary phase (14 h).…”
Section: Discussionmentioning
confidence: 76%
“…Possible promoters of some chitinase genes in B. cereus and Bt exhibit homology with the -35 (TTGACA) and -10 (TATAAT) consensus sequences for an E. coli promoter and B. subtilis r A , indicating that the expression of these chitinase genes occurs during the vegetative growth phase [2,11,28,35]. However, the production of chitinase increased steadily during vegetative growth and reached a maximum after 70 h [11].…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…B. thuringiensis is the most known insecticidal bacterium worldwide for the control of various plant pests. This bacterium produces many virulent factors such as chitinase [6,7] vegetative insecticidal proteins [8], and bacteriocins [9,10]. Bacteriocins are extracellularly released peptides or proteins affecting growth of closely related bacteria and several pathogenic species [9].…”
Section: Introductionmentioning
confidence: 99%